Interannual and long term variability of low level jetstream of the Asian summer monsoon. Issue 1 (1st January 2018) - Wilson, Shinu Sheela; Joseph, P. V.; Mohanakumar, K.; Johannessen, Ola M.
Abstract: Interannual and long-term variability of the low level jetstream (LLJ) of the Asian summer monsoon during June to September was studied using reanalysis wind data. In order to study the variability, the domain of the LLJ covering the Indian and west Pacific Oceans was divided into six regions (boxes) based on their physical characteristics. The long term variability of LLJ and its relation with Indian monsoon rainfall and El Nino index were analysed. The low level circulation over Indian Ocean becomes weak during the positive phase of El Nino Southern Oscillation leads to warmer sea surface temperature over Indian Ocean. The strength of the low level jet over India depends on the convective heating of the atmosphere and not on the strength of the south Indian Ocean trade wind ( ITz ) which remains a passive component of the LLJ. The LLJ flow through peninsular India is weaker and the flow south of peninsular India is stronger during the recent decades in association with increasing number of break monsoon days. The cross equatorial flow over west Pacific Ocean has statistically significant increasing trend related to the increasing convection in the west Pacific Ocean.